Why Unions Survive: Understanding How Unions Overcome the Free-Rider Problem - Murphy, Richard (Journal of Labor Economics, 2020)
This paper provides evidence for why individuals join unions instead of free riding. I model membership as legal insurance. To test the model, I use the incidence of news stories concerning allegations against teachers in the United Kingdom as a plausibly exogenous shock to demand for such insurance. I find that for every five stories occurring in a region, teachers are 2.2 percentage points more likely to be members in the subsequent year. These effects are larger when teachers share characteristics with the news story and can explain 45% of the growth in teacher union membership between 1992 and 2010.